A NON-ISOLATED HIGH STEP-UP GAIN DC-DC CONVERTER WITH SWITCHED INDUCTOR AND VOLTAGE MULTIPLIER CELL (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
The grid-connected inverters require the DC power at high voltage only. The low-voltage DC power produced by the solar photovoltaic (PV) panels cannot be directly connected to the input of grid-connected inverters. Hence, a DC-DC converter is necessary to be installed as an interface between the solar PV panels’ output and the grid-connected inverters. The interfacing DC-DC converter should have the capability to step-up the low DC voltage level of solar PV panels to the high DC voltage levels optimized to the grid-connected inverters. Such a high-voltage-gain DC-DC converter structure is proposed in this paper. The suggested non-isolated form of single-switch DC-DC converter topology can achieve relatively enhanced voltage gain at lower percentage of switch ON time itself by incorporating switched-inductors at the input side and a voltage multiplier cell at the output side of the converter. The topology has the additional advantage of reduced voltage and current stresses on the power switch and the diodes. The continuous inductor current mode operation of the converter is presented to validate the results of simulation of the converter at switch duty factor of 80%.
Keywords: Continuous inductor current mode; DC-DC converter; Duty factor; Enhanced voltage gain; Grid-connected inverters; Reduced switch voltage and current stresses